Computer system design : system-on-chip - Flynn, Michael J.; Luk, Wayne (Cambridge, Massachusetts : Wiley, 2011)
The next generation of computer designers will be concerned more about the elements of a system tailored to particular applications than with the details of processors and memories.
1. Introduction to the Systems Approach -- 2. Chip Basics: Time, Area, Power, Reliability, and Configurability -- 3. Processors -- 4. Memory Design: System-on-Chip and Board-Based Systems -- 5. Interconnect -- 6. Customization and Configurability -- 7. Application Studies -- 8. What's Next: Challenges Ahead.
Includes bibliographical references and index.
Keywords: SYSTEMS ON A CHIP